Estágio supervisionado e o pensar complexo na formação docente inicial dos(as) professores(as) da educação infantil no curso de pedagogia da UEG-UnU de Inhumas - Souza, Maria Erilânde Ferreira de (2021)
This dissertation is linked to the Educational Processes, Language and Technology concentration area of the Graduate Program in Education, Language and Technologies at the State University of Goiás. Its general objective was to analyze the Supervised Curricular Internship of the Pedagogy course at UEG-UnU of Inhumas in the initial teacher training of the Early Childhood Education teacher in the light of some cognitive operators of complex thinking. In this sense, we sought, from the following research question, a possibility to expand and reconnect knowledge: The Supervised Internship of the Pedagogy course at UEG-UnU de Inhumas presents evidence of complex thinking in the initial teacher training of the teacher ) of Early Childhood Education? The interest in researching the initial teacher training of the Early Childhood Education teacher arises from my own teaching practice. In addition, it is justified, given the fact that research related to Early Childhood Education is very recent and given the scenario that has been built, considering the training of teachers in the first stage of Basic Education, it is necessary to understand how the training has been a reality. initial teacher. In this sense, we highlight a specific moment in the initial teacher training process, which is the Supervised Curriculum Internship, which is the object of study of this research. The research is qualitative, with documental analysis and a case study conducted through questionnaires and semi-structured interviews with students and professors, who participated in the supervised Curricular Internship in 2019, in the Pedagogy course at UEG-UnU de Inhumas. Edgar Morin's Epistemology of Complexity (2004, 2010, 2015, 2016, 2018) was chosen as the theoretical framework, with some of the cognitive operators as guides for the analysis of the data collected. Complementing the theoretical framework, theoretical support was sought from the following authors: João Henrique Suanno (2013, 2014), Marilza Vanessa Rosa Suanno (2012, 2015), Maria Cândida Moraes (2007, 2008, 2014, 2016), Luciana Ostetto (2000) , 2011, 2012), Valdeniza da Barra (2016, 2017, 2020), Ecleide Furlanetto (2003, 2010, 2011), among others. The research found points that indicate the evidence of complex thinking in the initial teacher training process of the Early Childhood Education teacher of the students of the Pedagogy course at UEG-UnU de Inhumas. Being that the Supervised Curricular Internship proved to be the main way of meeting the articulation of knowledge in the process of becoming a teacher of Early Childhood Education and (re)constitution of pedagogical matrices.